Lack of Congruence between European Citizen Perspectives and Policies on Circular Economy - Repo, Petteri; Anttonen, Markku; Mykkänen, Juri; Lammi, Minna (European Journal of Sustainable Development, 2018)
The concept of circular economy has become a catchphrase for describing redesign of economies and industries towards better sustainability. The consideration of consumers holds a prominent role in the concept, yet consumers? concerns and hopes are not well accounted for. This article takes a forward-looking approach to the relationship between consumers and policies on circular economy. It analyses an extensive and systematically collected corpus of European citizen visions on desirable and sustainable futures from this perspective, and compares the outcomes to newly adopted circular economy policies in Europe. The article argues that European policies on circular economy should increasingly connect to energy and climate issues as well as social topics, if they are to build congruence between citizen and policy understandings, and thereby raise public acceptance for the concept. Keywords: circular economy, policy congruence, consumers, citizen visions, sustainability, topic modelling